Architectural solutions for contemporary dental clinics based on scientific research – a case study - Strojny, Rafał; Błasiak, Wiktoria (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2025)
Contemporary dental clinics are complex medical facilities in which functional efficiency, epidemiological safety and user comfort must be equally integrated into the design process. In recent years, especially after the COVID-19 pandemic, the importance of architectural solutions supporting aerosol control and optimised ventilation of treatment rooms has increased. The aim of this study is to analyse current trends and scientific research results concerning the design of the dental environment in the context of evidence-based design (EBD) principles and to present a conceptual model of a dental centre in Lublin, based on an integrated architectural and technical approach. The methodology includes a literature review, identification of key design aspects, and development of a model concept for a dental centre based on scientific research and in-depth interviews with medical staff at one of the dental clinics in Lublin. The results of the analysis indicate that the design of dental clinics requires an integrated approach, combining hygienic and epidemiological principles with psychological and ergonomic factors. The following are of key importance: proper ventilation and air purification systems, central sterilisation areas, a modular layout of treatment rooms, and the use of healing environment strategies, biophilic design, and acoustic solutions to improve user comfort.